Educational needs of family physicians and health care providers working in the family physician program of Iran - Mohammad Javad Kabir; Hasan Ashrafian Amiri; Seyyed Mozaffar Rabiee; Reza Momtahen; Rasoul Zafarmand; Seyyed Davoud Nasrollahpour Shirvani (Babol University of Medical Sciences, 2018)
BACKGROUND AND OBJECTIVE: One of the effective teaching strategies is the educational needs assessment. Need assessment is an important tool in designing, developing and evaluating continuous education programs. This study aimed to determine the educational needs of family physicians and health care providers working in Fars and Mazandaran provinces. METHODS: This cross-sectional study was conducted in the winter 2016 on urban family physicians and health care providers who were selected by systematic random sampling. The data collection tool was a researcher-made questionnaire consisting of 2 parts: individual variables (8 open and closed questions) and 50 subjects for physicians and 47 subjects for health care providers; its validity and reliability were confirmed. FINDINGS: Among 464 participants, 236 (50.9%) were physicians and 228 (49.1%) health care providers; 304 (65.5%) were female and the rest were male. Among the physicians, 26 (11.11%) did not require any training, and the rest declared at least one up to a maximum of 24 subjects as educational needs. The average number of subjects required training was 7.1±4.9. Among health care providers, 16 (7.0%) did not require any training, and 24 (10.5%) referred to the total 47 subjects as educational needs. The average number of required subjects was 24.16±16.6. There was a significant relationship between educational needs and some of the individual and social variables (P<0.05). CONCLUSION: This study showed that the educational needs of physicians are low and health care providers are high.